Harmonious fellowship of sexuality diverse Christians in the Maranatha Reformed Church of Christ - Alfred M. Rivombo (Verbum et Ecclesia)
The aim of this study was to investigate the challenges and experiences that impact harmonious fellowship among sexuality diverse Christians, and to explore strategies for sustaining such fellowship. It used the stance of Maranatha Reformed Church of Christ (MRCC) regarding the membership of homosexual persons as a case study. The research approach that was applied was qualitative. The researcher started by employing an opportunistic sampling strategy by advertising the research project to the church community and inviting volunteer participants. Because of insufficient responses, the researcher employed opportunistic and snowballing strategies by recruiting a few and requesting them to identify potential participants, resulting in 12 participants. Data were generated through semi-structured one-on-one interviews. The researcher used a thematic data analysis method. The researcher adhered to the prescribed protocol to guarantee compliance with study ethics. The findings highlight the significance of self-acceptance and transparent discussion in promoting mutual tolerance and inclusivity among Christians, despite contradictory perspectives on homosexuality. Participants who support full membership for non-heterosexuals without solemnising their marriages hope to allow time for open dialogue. Others advocate for allowing ministers to solemnise such marriages.